Chordate PIAS proteins act as conserved repressors of the TRAF6 self-polyubiquitination. (March 2020) - Fu, Xianan; Wang, Ruihua; Li, Mingshi; Yan, Xinyu; Huang, Huiqing; Li, Jin; Chen, Shenghui; Yue, Zirui; Chen, Shangwu; Li, Yingqiu; Dong, Meiling; Xu, Anlong; et al.
Abstract: In mammals, PIAS proteins are important SUMO E3 ligases and act as versatile regulators of over sixty different proteins, including components from the NF-κB pathways. But the PIAS functions are not well-understood due to complicated molecular mechanisms and multiple gene paralogs with overlapping roles, which is especially true in lower vertebrates where dedicated studies are scarce. As a basal chordate with a single PIAS gene, amphioxus is a convenient model to study PIAS from the evolutionary perspective. TRAF6 is a critical adaptor of the NF-κB pathways but it is not known whether TRAF6 is regulated by PIAS. Here we discover that in mammalian cells, amphioxus PIAS inhibited NF-κB activation by co-localizing and binding with TRAF6. The interaction relied on the N-terminal SAP and PINIT domains of PIAS. TRAF6 is an E3 ubiquitin ligase, which initiates downstream NF-κB signaling by promoting its self-ubiquitination. Both amphioxus SUMO1 and Ubc9 (SUMO E2 ligase) could suppress TRAF6 self-ubiquitination and NF-κB activation, suggesting that the SUMOylation activity competed away the ubiquitination activity of TRAF6. However, we show that the wild-type PIAS and the mutant PIAS without SUMO E3 ligase activity both could inhibit TRAF6-mediated NF-κB activation by reducing TRAF6 self-ubiquitination. This implies that SUMO ligase activity is not the only mechanism for PIAS to negatively regulate TRAF6. Finally, we tested the interactions between human PIAS1-4 and TRAF6. It reveals that human PIAS1, 3 and 4, but not 2, were able to repress NF-κB activation by reducing TRAF6 self-ubiquitination. Taken together, our study discovers a conserved regulatory interaction between chordate PIAS and TRAF6. It therefore sheds light on the complicated role of PIAS in immune regulation, and may help to understand the PIAS functions in other lower chordate taxa, such as jawless and jawed fishes. Highlights: In amphioxus, PIAS can suppress NF-κB activation by inhibiting the self-ubiquitination of TRAF6. SUMOylation inhibits the ubiquitination of TRAF6, but PIAS may not solely rely on its SUMO ligase activity to inhibit TRAF6. This functional mechanism is preserved in human PIAS1, 3 and 4, but not PIAS2.